MiR‐1253 exerts tumor‐suppressive effects in medulloblastoma via inhibition of CDK6 and CD276 (B7‐H3). (30th March 2020) - Kanchan, Ranjana K.; Perumal, Naveenkumar; Atri, Pranita; Chirravuri Venkata, Ramakanth; Thapa, Ishwor; Klinkebiel, David L.; Donson, Andrew M.; Perry, Deborah; Punsoni, Michael; Talmon, Geoffrey A.; Coulter, Donald W.; Boue', Daniel R.; et al.
Abstract: Of the four primary subgroups of medulloblastoma, the most frequent cytogenetic abnormality, i17q, distinguishes Groups 3 and 4 which carry the highest mortality; haploinsufficiency of 17p13.3 is a marker for particularly poor prognosis. At the terminal end of this locus lies miR‐1253, a brain‐enriched microRNA that regulates bone morphogenic proteins during cerebellar development. We hypothesized miR‐1253 confers novel tumor‐suppressive properties in medulloblastoma. Using two different cohorts of medulloblastoma samples, we first studied the expression and methylation profiles of miR‐1253. We then explored the anti‐tumorigenic properties of miR‐1253, in parallel with a biochemical analysis of apoptosis and proliferation, and isolated oncogenic targets using high‐throughput screening. Deregulation of miR‐1253 expression was noted, both in medulloblastoma clinical samples and cell lines, by epigenetic silencing via hypermethylation; specific de‐methylation of miR‐1253 not only resulted in rapid recovery of expression but also a sharp decline in tumor cell proliferation and target gene expression. Expression restoration also led to a reduction in tumor cell virulence, concomitant with activation of apoptotic pathways, cell cycle arrest and reduction of markers of proliferation. We identified two oncogenic targets of miR‐1253, CDK6 and CD276, whose silencing replicated the negative trophic effects of miR‐1253. These data reveal novel tumor‐suppressive properties for miR‐1253, i.e., (i) loss of expression via epigenetic silencing; (ii) negative trophic effects on tumor aggressiveness; and (iii) downregulation of oncogenic targets.